Quality in Higher Education: a Thoughtful Analysis on the Management of its Processess at Educational Centers of Latin America - Manuel Villarruel Fuentes (Universidad Autónoma de Madrid, 2016)
The concept of quality and its establishment within the higher educational institutions imposes a set of requirements that make it a problem to solve. The efforts to reach understanding and assurance have been directed toward the indoctrination of human resources, based on an academician rhetoric, which led even to ignore the guiding concepts that come from the social sciences. Obviously, this pragmatic approach does not help to clarify the causes of social resistance in trying to implement it.